The Effects of Integrating Social Learning Environment with Online Learning - Miroslava Raspopovic (Athabasca University Press, 2017)
The aim of this paper is to present the learning and teaching styles using the Social Learning Environment (SLE), which was developed based on the computer supported collaborative learning approach. To avoid burdening learners with multiple platforms and tools, SLE was designed and developed in order to integrate existing systems, institutional learning, management systems, and Facebook. With SLE, a learner is exposed to instructional learning material, problem-based, project-based, and social learning. This work focuses on presenting and analyzing effectiveness of implemented teaching and learning scenarios that are used by means of SLE. This study investigates the use of SLE as a learning environment and it examines student satisfaction and online activity while using it. The aim is to evaluate the overall effectiveness of integrating SLE with online learning and to determine how using SLE effects student learning. This analysis points out the advantages and disadvantages of using SLE in online learning and provides recommendations for future improvements.